Barriers to the effective exploitation of migrants' social and cultural capital in hospitality and tourism: A dual labour market perspective. (March 2022) - Hack-Polay, Dieu; Mas, Francesca Dal; Mahmoud, Ali B.; Rahman, Mahfuzur
Abstract: This article examines migrants' labour market entry experiences and positions in hospitality and tourism from a dual labour market theory standpoint. We conducted thirty interviews with migrants from Latin America, the Middle East, and Sub-Saharan Africa. The transcripts were first analysed through an open coding framework. That was followed by emotion and sentiment analyses for the interviewees' transcripts using Natural Language Processing approach (NLP) with a programming code written in Python. This article found that migrants' high representation in tourism and hospitality is linked to the immense cultural capital they harbour. However, migrants are often at the sector's lower end and fail to build on their social and cultural capital. The research contributes to the understanding that migrants' positions within tourism and hospitality are misaligned with migrants' credentials. Ethnicity impacts job search success and attainment of higher ranks significantly. The underemployment of migrants in hospitality and tourism leads to human capital loss for both migrants and host economies.